Enhanced thermal stability and flame retarding properties of recycled polyethylene based wood composites via addition of polyethylene/nanoclay masterbatch. (1st July 2013) - Gong, G; Nyström, B; Joffe, R
<x xml:space="preserve">Abstract</x> Barrier and mechanical properties of wood powder composites based on recycled polyethylene (RPE) were modified using a commercial nanoclay masterbatch. X-ray diffraction, dynamic rheology and thermogravimetric analysis measurements showed that nanoclay from the selected masterbatch was well dispersed and formed a percolation network in both virgin and RPEs. The resulting nanocomposites promoted the thermal stability of matrix significantly. Modification efficiency of nanoclay, however, was evidently influenced by the type of matrix, where the strongest effect was achieved in a low viscosity virgin high density PE. The masterbatch was incorporated into an industrial formula designed extrusion quality RPE/wood flour composite. Processing procedures, mainly compounding cycles, and material composition, mainly clay content and type of coupling agent, were optimised. Two extrusion cycles led to higher uniformity of resulting composites than one cycle. Addition of a coupling agent, which has medium viscosity and plenty functional groups, led to enhanced tensile strength. The twice compounded composites were well stiffened and strengthened via combination of 6 wt-% clay and medium viscosity coupling agent. All composites without the addition of nanoclay burned faster after ignition and dripped much earlier and more compared to the composites containing nanoclay even with as small amount as 3 wt-% and being compounded once. The material with 6 wt-% clay showed the best sample integrity and burned slowest of all the tested composites. Furthermore, no dripping during combustion was seen for this material. This study shows that the incorporation of nanoclay using the selected masterbatch can effectively improve the flame retarding properties of RPE based wood composites.